Communication skills profile - Tosca, Elena (Jossey-Bass Pfeiffer, 1997)
The Communication Skills Profile was designed to help people who want to gain a thorough knowledge of the processes of communication and to improve their effectiveness as communicators. It focuses on two main areas essential for effective communication: Expressing one’s opinions effectively, Listening to and understanding others.